Synthesis of PtCuFe alloy nanoframes with high-index facets for efficient electro-oxidation of liquid fuels. (1st May 2022) - Yu, Lei; Li, Binsheng; Wang, Qiushi; Chai, Zhenquan; Liu, Lili; Ma, Pengju; Tai, Xishi; Lv, Yipin; Zhang, Pengfang; Gao, Daowei
Highlights: 3-Dimensional Pt-based trimetallic nanoframe with high-index facets was synthesized. The defects and open framework contribute to increase the electrocatalytic activity. This work put forward a promising way to design high active site of electrocatalyst. Abstract: By controlling the structure, surface and composition of Pt-based ternary alloy nanocrystals, the electro-catalytic performances of Pt-based catalysts can be improved effectively. In this paper, a one-pot method for synthesis of PtCuFe nanoframes (PtCuFe NFs) with tunable structure and defect density is reported. By controlling the heating mode and the type of ligand, then changing the nucleation/growth kinetics, two types of PtCuFe NFs were obtained. These types of catalysts exhibited excellent electro-catalytic performance for methanol electrooxidation (MOR) and formic acid electrooxidation (FAOR). Specifically, the dendritic nanoframes (d-NFs) showed high electro-catalytic activity for MOR and FAOR, which were 8.34 times and 3.68 times higher than commercial Pt/C, respectively. The stability was also greatly improved. The excellent electrocatalytic activity of PtCuFe NFs is attributed to the defect sites of high-index facets and open framework structures. This strategy provides a new idea for improving the electrocatalytic performance of Pt-based catalysts.